2013
DOI: 10.1186/1476-4598-12-123
|View full text |Cite
|
Sign up to set email alerts
|

MiR-451 inhibits cell growth and invasion by targeting MIF and is associated with survival in nasopharyngeal carcinoma

Abstract: BackgroundMiRNAs play important roles in diverse biological processes including tumorigenesis. However, little is known about the function and mechanism of miR-451 in nasopharyngeal carcinoma (NPC).MethodsQuantitative RT-PCR was used to quantify miR-451 expression in NPC cell lines and clinical tissues. Kaplan-Meier curves were used to estimate the association between miR-451 expression and survival. The MTT, colony formation, Transwell migration and invasion assays, and a xenograft model were performed. A miR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
70
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(73 citation statements)
references
References 40 publications
3
70
0
Order By: Relevance
“…Dysregulation of miRNAs has been found to cause several pathological states by modulating cell autophagy [24]. According to previous studies, miR-222 helps to regulate of pathological cardiac remodeling and heart failure by mediating cardiomyocyte autophagy [25], miR-124 is involved autophagy in the peripheral blood from AS patients [26], and miRNA let-7i induces autophagy to protect T cells from apoptosis [27].…”
Section: Discussionmentioning
confidence: 99%
“…Dysregulation of miRNAs has been found to cause several pathological states by modulating cell autophagy [24]. According to previous studies, miR-222 helps to regulate of pathological cardiac remodeling and heart failure by mediating cardiomyocyte autophagy [25], miR-124 is involved autophagy in the peripheral blood from AS patients [26], and miRNA let-7i induces autophagy to protect T cells from apoptosis [27].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, miRNAs have been shown to be involved in the regulation of cellular behaviors, including differentiation and development, metabolism, proliferation, apoptosis, viral infection and tumor genesis [21,22], and dysregulation of miRNAs can result in a myriad of pathological states [23]. Recently, dozens of miRNAs are emerging as important negative or positive regulators of posttranscriptional gene expression and are considered critical for osteogenesis [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…miR-451 is known to exert various biological functions in cancer, infectious disease, cardiovascular and metabolic diseases. Previous studies have revealed that the dysregulation of miR-451 expression is involved in carcinogenesis and in tumor progression by affecting cell proliferation, cell-cycle distribution, migration, and invasion (Li et al, 2013;Liu et al, 2013;Tian et al, 2012). Furthermore, a recent study showed that miR-451 regulates dendritic cell cytokines and suppresses neutrophil chemotaxis via downregulation of p38 MAPK phosphorylation (Murata et al, 2014;Rosenberger et al, 2012).…”
Section: Introductionmentioning
confidence: 95%